Acute heart failure after non‐cardiac surgery: incidence, phenotypes, determinants and outcomes. (7th February 2023) - Gualandro, Danielle M.; Puelacher, Christian; Chew, Michelle S.; Andersson, Henrik; Lurati Buse, Giovanna; Glarner, Noemi; Mueller, Daria; Cardozo, Francisco A.M.; Burri‐Winkler, Katrin; Mork, Constantin; Wussler, Desiree; Shrestha, Samyut; et al.
Abstract: Aims: Primary acute heart failure (AHF) is a common cause of hospitalization. AHF may also develop postoperatively (pAHF). The aim of this study was to assess the incidence, phenotypes, determinants and outcomes of pAHF following non‐cardiac surgery. Methods and results: A total of 9164 consecutive high‐risk patients undergoing 11 262 non‐cardiac inpatient surgeries were prospectively included. The incidence, phenotypes, determinants and outcome of pAHF, centrally adjudicated by independent cardiologists, were determined. The incidence of pAHF was 2.5% (95% confidence interval [CI] 2.2–2.8%); 51% of pAHF occurred in patients without known heart failure ( de novo pAHF), and 49% in patients with chronic heart failure. Among patients with chronic heart failure, 10% developed pAHF, and among patients without a history of heart failure, 1.5% developed pAHF. Chronic heart failure, diabetes, urgent/emergent surgery, atrial fibrillation, cardiac troponin elevations above the 99th percentile, chronic obstructive pulmonary disease, anaemia, peripheral artery disease, coronary artery disease, and age, were independent predictors of pAHF in the logistic regression model. Patients with pAHF had significantly higher all‐cause mortality (44% vs. 11%, p  < 0.001) and AHF readmission (15% vs. 2%, p  < 0.001) within 1 year than patients without pAHF. After Cox regression analysis, pAHF was an independent predictor of all‐cause mortality (adjusted hazard ratio [aHR] 1.7 [95% CI 1.3–2.2]; p  < 0.001) and AHF readmission (aHR 2.3 [95% CI 1.5–3.7]; p  < 0.001). Findings were confirmed in an external validation cohort using a prospective multicentre cohort of 1250 patients (incidence of pAHF 2.4% [95% CI 1.6–3.3%]). Conclusions: Postoperative AHF frequently developed following non‐cardiac surgery, being de novo in half of cases, and associated with a very high mortality. Abstract : Incidence, phenotypes, determinants and outcomes of acute heart failure after non cardiac surgery. aHR, adjusted hazard ratio; CAD, coronary artery disease; CI, confidence interval; COPD, chronic obstructive pulmonary disease; CVD, cerebrovascular disease; HF, heart failure; HFmrEF, heart failure with mildly reduced ejection fraction; HFpEF, heart failure with preserved ejection fraction; HFrEF, heart failure with ejection fraction; PAD, peripheral artery disease; pAHF, postoperative acute heart failure; y, years.